2001
DOI: 10.1111/j.1151-2916.2001.tb00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of β‐Si3N4: III, Effect of Rare‐Earth (RE = La, Nd, Gd, Y, Yb, and Sc) Oxide Additives

Abstract: ␤-Si 3 N 4 ceramics sintered with a series of rare-earth (RE ‫؍‬ La, Nd, Gd, Y, Yb and Sc) oxide additives were fabricated by hot pressing and subsequent annealing. Their microstructures, lattice oxygen contents, and thermal conductivities were evaluated. Mean grain size increased, while lattice oxygen content decreased, and hence, thermal conductivity increased with decreasing ionic radius of the rare-earth element. In all cases, a marked change was observed in the order of ionic radius from La to Nd to Gd, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(47 citation statements)
references
References 23 publications
1
45
0
1
Order By: Relevance
“…Figure 35(c) shows that the thermal anisotropy increases gradually with increased Y 2 O 3 : SiO 2 molar ratio, which seems to correlate with the increased grain size. Actually, this should be attributed to the increased aspect ratio with increased Y 2 O 3 : SiO 2 molar ratio, thereby resulting in a higher degree of orientation during HP and subsequent annealing [62,135]. However, it is found that thermal anisotropy is limited to below 30% in hot-pressed Si 3 N 4 regardless of the processing conditions.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Figure 35(c) shows that the thermal anisotropy increases gradually with increased Y 2 O 3 : SiO 2 molar ratio, which seems to correlate with the increased grain size. Actually, this should be attributed to the increased aspect ratio with increased Y 2 O 3 : SiO 2 molar ratio, thereby resulting in a higher degree of orientation during HP and subsequent annealing [62,135]. However, it is found that thermal anisotropy is limited to below 30% in hot-pressed Si 3 N 4 regardless of the processing conditions.…”
Section: Resultsmentioning
confidence: 82%
“…They showed that the thermal conductivity along the direction parallel to the HP is 36% lower than that along the direction perpendicular to the HP at 20 • C. Moreover, this value was found to decrease to 15% at 1300 • C. Kitayama et al conducted a series of studies on the thermal conductivity of hot-pressed Si 3 N 4 , including the roles of the starting powders [53], lattice oxygen [58] and RE oxide additives [62], as summarized in figure 35. Figure 35(d) shows the two cases for measuring thermal conductivity by the laser flash method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To enhance the thermal conductivity, sintering additives should play a dual role of promoting densification and removing lattice oxygen. Among the rare-earth oxides, Y 2 O 3 and Yb 2 O 3 are the most promising additives for enhancing the thermal conductivity of β-Si 3 N 4 ceramics [12]. Because of its economic advantage over hot isostatic pressing and the improved thermal and mechanical properties compared with Si 3 N 4 ceramics produced by pressureless sintering, gas pressure sintering has been widely used to produce β-Si 3 N 4 ceramics with high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%